2014
DOI: 10.1038/mi.2013.127
|View full text |Cite
|
Sign up to set email alerts
|

Small alveolar macrophages are infected preferentially by HIV and exhibit impaired phagocytic function

Abstract: HIV-1-infected persons are at higher risk of lower respiratory tract infections than HIV-1-uninfected individuals. This suggests strongly that HIV-infected persons have specific impairment of pulmonary immune responses, but current understanding of how HIV alters pulmonary immunity is incomplete. Alveolar macrophages (AMs), comprising small and large macrophages, are major effectors of innate immunity in the lung. We postulated that HIV-1 impairs pulmonary innate immunity through impairment of AM physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
145
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 49 publications
6
145
2
Order By: Relevance
“…In high transmission regions, most TB cases in HIV-individuals result from recent Mycobacterium tuberculosis (Mtb) infection indicating that in these individuals the lung is more permissive for the establishment or progression of primary infections (3). Recent studies have reported that alveolar macrophage (AM) proteolytic function and mycobacterial antigen-specific Th1 CD4 1 T-cell responses in the lung are impaired in asymptomatic HIV-infected, antiretroviral therapy (ART)-naive persons (4)(5)(6). These findings indicate that HIV alters both innate and adaptive immunity in the lung to render HIV-infected individuals incapable of mounting adequate pulmonary immune responses to control Mtb.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…In high transmission regions, most TB cases in HIV-individuals result from recent Mycobacterium tuberculosis (Mtb) infection indicating that in these individuals the lung is more permissive for the establishment or progression of primary infections (3). Recent studies have reported that alveolar macrophage (AM) proteolytic function and mycobacterial antigen-specific Th1 CD4 1 T-cell responses in the lung are impaired in asymptomatic HIV-infected, antiretroviral therapy (ART)-naive persons (4)(5)(6). These findings indicate that HIV alters both innate and adaptive immunity in the lung to render HIV-infected individuals incapable of mounting adequate pulmonary immune responses to control Mtb.…”
mentioning
confidence: 88%
“…Recently, we reported that AM phagosomal proteolysis function is impaired in asymptomatic HIV-infected ART-naive adults (6). To determine whether use of ART is associated with improvement in this functional defect, we used the flow cytometry-based reporter bead assay to measure phagosomal proteolysis in AM Next, we investigated Th1 and Th17 mycobacteria-and influenza-specific CD4 1 T-cell responses in BAL and peripheral blood using an intracellular cytokinestaining assay.…”
Section: Am Phagosomal Proteolysis Function Is Impaired In Hiv-infectmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been attributed to several mechanisms, including 1) resilience of airway Th1 and Th17 cells [21,23] as well as large, as opposed to small, alveolar macrophages [24] to HIV infection and dysfunction; 2) relatively high frequencies of mucosal HIV-specific polyfunctional CD4 + T-cells in the lungs; 3) a lesser mass of HIV-susceptible secondary lymphoid tissue relative to that of the GIT [20]; and 4) the apparent efficacy of the pulmonary HIV-specific cytotoxic T-cell response, manifested clinically as an alveolitis [25].…”
Section: Immunosuppressive Mechanisms Of Hiv Infection and Smokingmentioning
confidence: 99%
“…These approaches have provided valuable insights into intranuclear transport and integration site selection in infected cell nuclei. RNA FISH approaches have been utilized to monitor HIV-1 expression at the single-cell level in samples from infected patients, providing new insights in the tissue distribution of productively infected cells (28) and, when combined with DNA FISH, potential latent cell reservoirs in the body (29).…”
mentioning
confidence: 99%